International Cooperation and Negotiated Settlements for Transnational Bribery: A Study of the Odebrecht Case - Raquel de Mattos Pimenta; Otavio Venturini (Revista Direito GV)
Abstract Transnational regulation of bribery involves several increasingly complex forms of cooperation among enforcement authorities. International investigative cooperation allows a foreign authority to assist another on criminal and/or civil investigations, through requests of mutual legal assistance, rogatory letters, as well as joint investigative teams. Sanction-based cooperation helps different authorities to transfer or extradite persons and recover proceeds of corruption to the victims. More recently, there has been a rise in cooperation in negotiated settlements with the accused. Settlement cooperation may entail joint resolutions or the coordination of settlement clauses. This paper focuses on how these three modes of cooperation intersect in cases with successive negotiated settlements. We use the Odebrecht case settlements to unpack the relation between investigative, sanction-based, and settlement cooperation in three case studies: the joint resolutions between the company and Brazil, Switzerland, and the United States, as well as two local agreements with the Dominican Republic and with Peru. We evidence how these modes of cooperation can reinforce or undermine one another. Beyond illustrating different cooperation dynamics, we also explore the role of sequencing. The existence of a previous joint resolution affects the developments of the subsequent agreements, but in different ways from those previously mapped by the literature.